2015
DOI: 10.1016/j.sbspro.2015.01.1068
|View full text |Cite
|
Sign up to set email alerts
|

“Exploratory” and “Descriptive” Aspects of Environmental Psychology Course within the Interior Design Education

Abstract: Identifying human attachment to the environment by developing different degrees, spatial ranges and dimensions, this study aims to further the growing body of knowledge about the discipline of Environmental Psychology within the process of interior design solving problems. Environmental Psychology provides an analytic point of view up on the existing built environment with a rich and diverse set of quantitative indicators for characterizing spaces in many ways that are potentially relevant to a variety of psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The role of environmental psychology was examined in the educational roadmap of interior design in the recent researches. Yalçin (2015) emphasized student inquiry in terms of psycho-social factors affecting people, directing spatial design and identity in order to establish their analysis, providing "Exploratory" and "Descriptive" aspects to the design problem. Their exploration revealed that the relationships with interior and exterior spaces provide not only emotional and psychological affordances but also cognitive and social affordances which satisfy the sense of place, integrate and enable engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The role of environmental psychology was examined in the educational roadmap of interior design in the recent researches. Yalçin (2015) emphasized student inquiry in terms of psycho-social factors affecting people, directing spatial design and identity in order to establish their analysis, providing "Exploratory" and "Descriptive" aspects to the design problem. Their exploration revealed that the relationships with interior and exterior spaces provide not only emotional and psychological affordances but also cognitive and social affordances which satisfy the sense of place, integrate and enable engagement.…”
Section: Discussionmentioning
confidence: 99%
“…To meet these purposes classroom activities brings real world problematics for being solve, allowing the alumni to observe and experiment in environments that consider differences as their learning styles (Yalçin, 2015). Although these programs have a positive and significant impact in the way the students perceived and solve real world problems, research had found that some aspects related to their creative endeavor may be missing in the educational curricula by not considering variables and traits entangled to creativity and innovation, as curiosity does.…”
Section: Discussionmentioning
confidence: 99%
“…To this day, teaching methods tend to balance both, the creative process with a critical awareness of objective criteria to meet the design purposes. Regularly, in these programs, design curricula consider aspects as learning styles as individual traits with an active repercussion in the student's outcomes (Yalçin, 2015). But what other sources of variability do we have?…”
Section: Teaching Methods To Be Creativementioning
confidence: 99%
See 1 more Smart Citation
“…While light and color are flexible and can change easily by inhabitant"s mood (Wardono, Hibino, & Koyama, 2012). Interior space form is one of the main design factors that can have special effects on inhabitant"s emotions (Karslı, 2015;Yalçin, 2015).…”
Section: Introductionmentioning
confidence: 99%